Home-made or imported: On the possibility for renewable electricity autarky on all scales in Europe. (November 2019) - Tröndle, Tim; Pfenninger, Stefan; Lilliestam, Johan
Abstract: Because solar and wind resources are available throughout Europe, a transition to an electricity system based on renewables could simultaneously be a transition to an autarkic one. We investigate to which extent electricity autarky on different levels is possible in Europe, from the continental, to the national, regional, and municipal levels, assuming that electricity autarky is only possible when the technical potential of renewable electricity exceeds local demand. We determine the technical potential of roof-mounted and open field photovoltaics, as well as on- and offshore wind turbines through an analysis of surface eligibility, considering land cover, settlements, elevation, and protected areas as determinants of eligibility for renewable electricity generation. In line with previous analyses we find that the technical-social potential of renewable electricity is greater than demand on the European and national levels. For subnational autarky, the situation is different: here, demand exceeds potential in several regions, an effect that is stronger the higher population density is. To reach electricity autarky below the national level, regions would need to use very large fractions or all of their non-built-up land for renewable electricity generation. Subnational autarky requires electricity generation to be in close proximity to demand and thus increases the pressure on non-built-up land especially in densely populated dense regions where pressure is already high. Our findings show that electricity autarky below the national level is often not possible in densely populated areas in Europe. Highlights: We show in which parts of Europe local electricity autarky is possible in principle. More than 3000 European municipalities cannot be autarkic due to insufficient land area. Deploying rooftop PV is key for autarky, if storage can be handled. Opposition to dense local generation will diminish possibility of autarky. Cooperation between municipalities and regions can relieve local pressure on land.